1 - Mafeje and ‘Authentic Interlocutors’: an appraisal of his epistemology - Bongani Nyoka (African Sociological Review, 2013)
Very little is known in the South African academy about Archie Mafeje’s theoretical writings. When those who knew him, or those who knew of him, do write, they very often focus on matters that have little to do with his work. This paper seeks to remedy this deficiency in the said writings by attempting to grapple with his epistemological and methodological approach to the social sciences – his notions of ‘authentic interlocutors’ and the ‘discursive method’. The paper affirms no unique position as such; its contribution consists, for the most part, in its exposition of Mafeje’s work.